Confusión grafemática de -b-, -u-, -v- en tres documentos mansucritos de la primera oleada de la Conquista de América - Aleksandrova, Daniela (Yearbook of the Department of Foreign Languages and Cultures, 2024)
This article studies the confusion between the graphemes -b-, -u-, and -v-, typical of 16th-century Spanish, in three manuscripts from the first wave of the Spanish Conquest: two versions of Lope de Aguirre’s letter to King Philip II, and Vázquez y Almesto’s Relación de Omagua y El Dorado. The article applies a descriptive, comparative, and document analysis method.